Exploring Mathematical Concepts in Batik Sidoluhur Solo - Naufal Ishartono; Dewi Ayu Ningtyas (International Journal on Emerging Mathematics Education, 2021)
Many ethnomathematical studies examine the existence of mathematics concepts in Indonesian cultural products where batik is one of them. However, there is a lacunae from previous studies that examine the existence of mathematical concepts in Batik Sidoluhur. Therefore, the current study aims to explore mathematical concepts in Batik Sidoluhur, such as geometry, algebra, arithmetic, and statistics. The study used ethnography as an approach by answering four principal questions, namely "where do I start looking?", "how do I find it?", "how do I recognize that it has found something significant?" and "how to understand what it is?". By answering the questions, researchers managed to examine the mathematical concept contained in Batik Sidoluhur. From the four mathematical concepts explored, namely geometry, algebra, statistics, and arithmetic, only the concept of geometry is contained in Batik Sidoluhur and has been confirmed by a geometry expert. Sub-concepts of geometry found are (1) sub-concepts of geometry transformations such as translation and reflection, (2) plane geometry such as rhombuses, rectangles, triangles, and circles, and (3) congruence. It is hoped that the results of this study can be used as materials to promote Batik Sidoluhur to the younger generation through contextual and meaningful mathematics learning. In this article also explained how to use the context of Batik Sidoluhur in mathematics learning.